Assessment of Caregiver’s Knowledge, Complementary Feeding Practices, and Adequacy of Nutrient Intake from Homemade Foods for Children of 6–23 Months in Food Insecure Woredas of Wolayita Zone, Ethiopia - Abeshu, Motuma Adimasu; Adish, Abdulaziz; Haki, Gulelat D.; Lelisa, Azeb; Geleta, Bekesho (Frontiers in Nutrition, 2016)
Complementary feeding should fill the gap in energy and nutrients between estimated daily needs and amount obtained from breastfeeding from 6 month onwards. Homemade complementary foods, however, are often reported for inadequacy in key nutrients despite reports of adequacy for energy and proteins. The aim of this study was to assess caregiver’s complementary feeding knowledge, feeding practices, and to evaluate adequacy daily intakes from homemade complementary foods for children of 6 – 23 months in food insecure woredas of Wolayita zone, Ethiopia. A cross sectional study assessing mothers/caregiver’s knowledge and complementary feeding practice, adequacy of daily energy and selected micronutrient intakes using weighed food record method. Multi-stage cluster sampling method was also used to select 68 households. Caregivers had good complementary feeding knowledge. Sixty (88.2%) children started complementary feeding at 6 months and 48 (70.6%) were fed 3 or more times per day. Daily energy intake however was significantly lower (P<0.05) than estimated daily needs, with only 151.25, 253.77 and 364.76 (kcal/day)for 6–8, 9–11 and 12–23 months, respectively. Similarly, Ca and Zn intakes (mg/day) were below the daily requirements (p=0.000), with value of 37.76, 0.96; 18.83, 1.21; 30.13, 1.96; for the 6-8, 9-11 and 12-23 months, respectively. Significant shortfall in daily intake of Fe (p=0.000) was observed among the 6-8 and 9-11months (3.25, 4.17mg/day, respectively), even accounting for high bioavailability. The complementary foods were energy dense. Daily energy, Ca, Zn and Fe (except 12 – 23 months) intake, however, was lower than estimated daily requirements.